Game-Based Learning for Mathematics Lesson on 3rd Grade Elementary School - Tanudidjaja, Miquel Jan; ., Bernadhed; Pranata, Caraka Aji (Journal of Applied Informatics and Computing, 2025)
Integrating cutting-edge strategies to improve students' learning experiences has become increasingly important in the ever-changing world of education. This study investigates how third-grade students at SD Pius Purbalingga can benefit from using game-based learning as an instructional strategy to improve their mathematical education. The study focuses on how to hold children' attention and improve their knowledge of mathematics. The main subject of this study is the effectiveness of educational games in enhancing elementary school student's understanding of mathematics. A mathematics game was created to solve this problem by actively involving pupils and reiterating key mathematical ideas. This game-based strategy aimed to create an engaged and enjoyable learning experience for third-grade pupils with acceptable cognitive capacities. The findings suggest that students who played the math game significantly increased their involvement, comprehension, and memorization of mathematical ideas. This study adds to the growing evidence supporting using educational games as useful tools in mathematics instruction. The study's findings revealed increased academic performance among students, with male students experiencing a rise of 2.4% in their overall scores. In contrast, female students demonstrated a significantly higher increase of 8.5%, indicating a more pronounced advancement in their academic performance.